Reacting to Globalization Admirably through Management by Objectives - Tampubolon, Liosten Rianna Roosida Ully; Ahmad, Mauledy; Abidin, Ali Zaenal; Isma, As'ad; Nguyen, Phong Thanh (International Journal of Psychosocial Rehabilitation, 2020)
Indonesian individuals must have the option to react to globalization admirably. Globalization is in fact difficult to battle, yet the network must not be crushed and abandon globalization. On the off chance that the Indonesian individuals don’t need the personality and character of the network and its social riches to be lost in the hands of globalization, at that point the network must have a solid resistance component. Globalization may assault from all fronts, however with a solid network guard, the country’s way of life will be very much saved. The conservation of neighborhood culture will reinforce the personality of a country, since culture is an image of the personality and character of a country.